Language Suggestion in Online Advertising of Figure Skating Ice Shows - O. A. Selemeneva (Научный диалог, 2023)
The article is devoted to the problem of latent verbal influence on the attitudes of the addressee in the advertising sports discourse. The purpose of the work is to identify linguistic means that realize the suggestive potential in the advertising of figure skating ice shows. The analysis of media texts posted in the Russian social network “VKontakte” was carried out. 124 advertising texts for 2021—2023 were analyzed Methods of discursive and communicative-pragmatic analysis, content analysis, descriptive method were used. It has been established that the verbal component of the considered advertising texts in the social network “VKontakte” is characterized by a small volume, clear logical and compositional structuring, linguistic minimalism, substantiveness, expansion of the nominative case, as a result of which the range of linguistic means of suggestion used is limited. These include allusive anthroponyms (participate in the formation of 84% of advertising media texts), evaluative vocabulary (42 %), bifunctional declarative-exclamatory sentences (37 %), vocative sentences (21 %). It is concluded that the listed units reveal their suggestive potential by replacing rational justification with emotional argumentation; activation of different types of associations; the affective component of the impact, determined by the presence of sympathy specifically for domestic figure skaters; the effect of stereotypes of personalities and the background knowledge of the addressee.